Impact Of the Modeldiscovery Learningon the Outcomes of Learning Indonesian Language on Poetry Writing Materials for Grade Iv Students State Elementary School 104185 Sei Semayang District Sunggal District of Deli Serdang - Rengganis, Ayu; Rahmat Kartolo (International Journal of Educational Research Excellence (IJERE), 2025)
The problem in this study is the ability to write poetry in Grade IV of SD Negeri 104185 Sei Semayang without using the Discovery Learning learning model. What are the results of learning to write poetry in grade IV of SD Negeri 104185 Sei Semayang using the Discovery Learning learning model? This study aims to develop the results of learning to write poetry using the Discovery Learning learning model in Grade IV students of SD Negeri 104185 Sei Semayang. This is an experimental study (pre-experimental design) with a one-group pretest-posttest design using descriptive analysis and inferential statistical analysis, which was carried out in four meetings. The sample in the study was grade IV of SD Negeri 104185 Sei Semayang, comprising as many as 40 people. The results of the study revealed two important findings. First, the level of ability to write poetry without using the Discovery Learning learning model of Grade IV students of SD Negeri 104185 Sei Semayang obtained an average score of 65.26 with a mastery level of 55-65% with sufficient qualifications. Second, the level of poetry writing ability using the Discovery Learning learning model of fourth grade students of SD Negeri 104185 Sei Semayang obtained a score of 80.27 with a mastery level of 76% -85% with a good (B) qualification. It is concluded that the poetry-writing ability of fourth-grade students of SD Negeri 104185 Sei Semayang using the Discovery Learning learning model is better than not using the Discovery Learning learning model